2016
DOI: 10.1007/s10517-016-3322-5
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Changes in Mesenteric Lymph Nodes and Lymphocyte Subpopulation Composition in Experimental Ulcerative Colitis

Abstract: Morphological changes in the mesenteric lymph nodes of male C57Bl/6 mice and subpopulation composition of lymphocytes in these nodes were studied in experimental acute and chronic ulcerative colitis induced by sodium dextran sulfate. Acute and chronic ulcerative colitis was associated with the development of reactive changes in the mesenteric lymph nodes. These changes were of mixed type and were characterized by follicular hyperplasia and sinus reaction. The content of CD19(+) B cells in the mesenteric lymph … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…CD3 + CD8 + T cells specifically and directly kill target cells. Flow cytometry showed that the ratio of CD3 + CD4 + T lymphocytes and CD3 + CD8 + T lymphocytes in the UC model group was higher than normal controls, which was consistent with the findings of Postovalova's group [ 32 , 33 ]. In contrast, different doses of Garidisan, SASP, and Bupiyichangwan reduced the ratio of CD3 + CD4 + T lymphocytes and CD3 + CD8 + T lymphocytes in peripheral blood of UC rats.…”
Section: Discussionsupporting
confidence: 88%
“…CD3 + CD8 + T cells specifically and directly kill target cells. Flow cytometry showed that the ratio of CD3 + CD4 + T lymphocytes and CD3 + CD8 + T lymphocytes in the UC model group was higher than normal controls, which was consistent with the findings of Postovalova's group [ 32 , 33 ]. In contrast, different doses of Garidisan, SASP, and Bupiyichangwan reduced the ratio of CD3 + CD4 + T lymphocytes and CD3 + CD8 + T lymphocytes in peripheral blood of UC rats.…”
Section: Discussionsupporting
confidence: 88%
“…We have previously reported the increase of colonic CD8 + and CD25 + T cells in the DSS model of colitis related to disease worsening and increased histological damage [51], whereas both cell types were attenuated by TUS in the current study. We also observed an increase of CD4 + T cells and B220 + B cells in the MLN that may indicate a transition to a chronic state of the disease [52]. However, the upregulation of B220 + B cells in the spleen and MLN may contribute to gut homeostasis and attenuation of colitis while interacting with T regulatory cells [53].…”
Section: Discussionmentioning
confidence: 99%
“…It is pointed out that in some studies the onset of UC during the active period is related to the body's immunity [22]. Changes in the number and ratio of T lymphocytes subsets can reflect the body's cellular immune function [23]. T lymphocytes in patients with UC during the active period are mainly manifested as the imbalance of subsets under antigen stimulation, leading to the abnormalities of other inflammatory mediators, cytokines and inflammatory cells, thus causing intestinal mucosal inflammation and tissue damage [24,25].…”
Section: Adverse Reactionsmentioning
confidence: 99%